Factors Influencing Pedagogical Activities in Web 2.0 Technologies Integration: A Case of Three Universities in Tanzania - Kazoka, James E.; Wema, Evans F (University of Dar es Salaam Library Journal, 2021)
The study examined the factors influencing integration of Web 2.0 technologies in teaching and learning in three universities in Tanzania. Specifically, the study aimed to examine the extent to which Web 2.0 technologies are used in performing academic tasks, motives behind the integration of Web 2.0 technologies in teaching and learning activities and factors influencing integration of Web 2.0 technologies in pedagogy activities. The study used the Unified Theory of Acceptance and Use of Technology. The study was conducted at Muhimbili University of Health and Allied Sciences, Sokoine University of Agriculture and University of Dar es Salaam. It involved 47 members of staff and 141 postgraduate students. A mixed approach was employed in the study. Accordingly, a cross-sectional survey alongside documentary review was used to collect data from randomly selected postgraduate students while purposive sampling was used to select faculty members. The findings show that Web 2.0 technologies were frequently used for some academic activities while others were used for social communication. Among the factors influencing integration of Web 2.0 are familiarity with the technologies, expertise on the use of Web 2.0, attitude towards the technologies and support on the use of such technologies. The study recommends that technical support on proper design and use of Web 2.0 tools should be provided in teaching and learning, and short courses and workshops should be organized for faculty members and students.